Project of Museum of History of Science and Technology in Chelyabinsk as a Means of Preserving Industrial Heritage in Urals during 1980s - E. S. Lakhtionova (Научный диалог)
This article explores the origins of the project for the Museum of the History of Science and Technology in Chelyabinsk. It discusses how its initiation and development coincided with the 1980s, a period in the USSR marked by a growing interest in preserving monuments of scientific and technological history. The novelty of this research lies in the lack of existing studies on this topic, as well as the incorporation of unique archival materials that are being introduced into scholarly discourse for the first time. The author identifies the prerequisites for the creation of the project and the reasons for its implementation specifically in Chelyabinsk. The article establishes the authorship of the project, outlines its scientific concept, and examines its alignment with the conceptual foundations of science and technology museums of that era. The author also clarifies the exact name of the museum based on regulatory and project documentation. The article reconstructs the decisionmaking process and content of governmental resolutions regarding the establishment of the museum, as well as the challenges faced during its implementation. The author concludes that the project to create the Museum of the History of Science and Technology in Chelyabinsk was reflective of a broader zeitgeist, where the efforts of the scientific community and the general public were focused on preserving monuments of industrial heritage. The substantive elements of the project also indicate a desire to museify remaining artifacts of the industrial past in the Urals.